Perilaku Konsumen Kopi: Proses Keputusan dan Kepuasan Konsumen Membeli Minuman Kopi Berlabel Fair Trade - Vista Uli Sihombing; Anna Fariyanti; Rachmat Pambudy (Institut Pertanian Bogor, 2023)
Fair Trade (FT) coffee has a higher production volume than other coffee certifications. This phenomenon is triggered by a shift that is influenced consumer behavior patterns. This study analyzes consumer characteristics, purchasing decisions, and satisfaction in buying FT coffee. A cross-sectional study with a quantitative approach was used as the research design. Data were obtained by distributing online questionnaires to 120 respondents using a voluntary sampling technique. Data were analyzed using descriptive analysis, Customer Satisfaction Index (CSI), and Importance Performance Analysis (IPA). The results showed that most respondents were male, with an undergraduate degree and unmarried status. Trends and easy to get drink influence the main reason for purchasing. The main source of information comes from friends who focus on the coffee's taste and flavor. Consumers will continue to buy coffee even though prices have increased. Through CSI calculation, customer satisfaction is worth 74.04%. The results of the IPA calculation show that the main attributes to be improved are price, sales location, and information provision. The results of this study can be used as information on developing a marketing strategy that is adjusted to evaluate consumer expectations. Keywords: characteristics, consumer behavior, fair trade coffee, purchasing decision, satisfaction